Cytotoxicity and Antimycobacterial Properties of Pyrrolo[1,2-a]quinoline Derivatives: Molecular Target Identification and Molecular Docking Studies - Katharigatta N. Venugopala; Vijayakumar Uppar; Sandeep Chandrashekharappa; Hassan H. Abdallah; Melendhran Pillay; Pran Kishore Deb; Mohamed A. Morsy; Bandar E. Aldhubiab; Mahesh Attimarad; Anroop B. Nair; Nagaraja Sreeharsha; Christophe Tratrat; et al. (MDPI AG, 2020)
A series of ethyl 1-(substituted benzoyl)-5-methylpyrrolo[1,2-a]quinoline-3-carboxylates 4a-f and dimethyl 1-(substituted benzoyl)-5-methylpyrrolo[1,2-a]quinoline-2,3-dicarboxylates 4g-k have been synthesized and evaluated for their anti-tubercular (TB) activities against H37Rv (American Type Culture Collection (ATCC) strain 25177) and multidrug-resistant (MDR) strains of Mycobacterium tuberculosis by resazurin microplate assay (REMA). Molecular target identification for these compounds was also carried out by a computational approach. All test compounds exhibited anti-tuberculosis (TB) activity in the range of 8-128 µg/mL against H37Rv. The test compound dimethyl-1-(4-fluorobenzoyl)-5-methylpyrrolo[1,2-a]quinoline-2,3-dicarboxylate 4j emerged as the most promising anti-TB agent against H37Rv and multidrug-resistant strains of Mycobacterium tuberculosis at 8 and 16 µg/mL, respectively. In silico evaluation of pharmacokinetic properties indicated overall drug-likeness for most of the compounds. Docking studies were also carried out to investigate the binding affinities as well as interactions of these compounds with the target proteins.